Systemic healing for complex families: a review of the eco-systemic structural family therapy model in social work and psychological practice - Cădariu, Ioana-Eva; Rad, Dana (Technium Sustainability, 2025)
Eco-Systemic Structural Family Therapy (ESFT) is a comprehensive intervention paradigm aimed at meeting the intricate requirements of multi-stressed families by integrating structural family therapy, ecological systems theory, trauma-informed principles, and neurodevelopmental insights. This review consolidates the theoretical underpinnings, essential elements, empirical findings, and areas of application for ESFT, emphasizing its significance in child welfare, juvenile justice, community mental health, and school-based social work. The paper emphasizes the adaptability, relational depth, and systemic reach of ESFT, drawing on data from both Western and non-Western contexts, including recent research from Eastern Europe. Although current empirical research indicates favorable results in child behavior, family dynamics, and inter-system collaboration, obstacles remain regarding implementation integrity, cultural adaptability, and the necessity for additional randomized controlled trials. The review advocates for the wider global adoption of ESFT, presenting it as a viable paradigm that intersects psychology and social work, with the potential to foster relational healing and systemic transformation.